2022
DOI: 10.1002/leap.1455
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, willingness, and resources to cover article publishing charges: The influence of age, position, income level country, discipline and open access habits

Abstract: The rise of open access (OA) publishing has been followed by the expansion of the Article Publishing Charges (APC) that moves the financial burden of scholarly journal publishing from readers to authors. We introduce the results of an international randomly selected sampled survey (N=3,422) that explores attitudes towards this pay-to-publish or Gold OA model among scholars. We test the predictor role of age, professional position, discipline, and income-level country in this regard. We found that APCs are perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…The perceived weak quality may have roots in different factors, including a probable loose reviewing (Togia and Korobili, 2014) leading to low-quality publications (Waller et al ., 2013) and predatory publishing (Tennant et al ., 2016; Swanberg et al ., 2020). Considered a global threat to science (Segado-Boj et al ., 2022), the APC-based model is believed to have the potential to tempt publishers to sacrifice quality for money (Walters, 2007) and thereby pull scientific publishing into vanity and absurdity, with high acceptance rates for affluent authors or institutions (Creaser, 2010; Mischo and Schlembach, 2011). As a tangible example, the so-called ‘peer-review lite’ approach, which is followed by mega journals and claimed to result in a quick publication via a simpler peer review process and higher acceptance rates (McVearry, 2020) is observed to be effective in a significant and growing percentage of publisher income (Butler, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived weak quality may have roots in different factors, including a probable loose reviewing (Togia and Korobili, 2014) leading to low-quality publications (Waller et al ., 2013) and predatory publishing (Tennant et al ., 2016; Swanberg et al ., 2020). Considered a global threat to science (Segado-Boj et al ., 2022), the APC-based model is believed to have the potential to tempt publishers to sacrifice quality for money (Walters, 2007) and thereby pull scientific publishing into vanity and absurdity, with high acceptance rates for affluent authors or institutions (Creaser, 2010; Mischo and Schlembach, 2011). As a tangible example, the so-called ‘peer-review lite’ approach, which is followed by mega journals and claimed to result in a quick publication via a simpler peer review process and higher acceptance rates (McVearry, 2020) is observed to be effective in a significant and growing percentage of publisher income (Butler, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…, 2017; Waller et al ., 2013; Tenopir et al ., 2017; Dalton et al ., 2020). The negative attitudes and the lack of motivation reportedly relate to several concerns, with the most important and prevalent being high costs, OA journal quality, impact, and prestige, reviewing quality, plagiarism and copyright violation, misinformation, and predatory journals (Togia and Korobili, 2014; Rodriguez, 2014; Yang and Li, 2015; Gaines, 2015; Nicholas et al ., 2015; Almahmud et al ., 2020; Edelmann and Schoßböck, 2020; O'Hanlon et al ., 2020; Scott et al ., 2021; Segado-Boj et al ., 2022). These concerns have formed the main topics of OA literature (Rodrigues et al ., 2016) and remained almost unchanged over years (Mabe and Mulligan, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Asai (2021b) investigated countries to which authors belong using large samples and found that authors from low‐income countries amounted to less than 1% of the total authors, whereas most authors in hybrid journals belonged to high‐income countries. Universities and other research institutes in high‐income countries often financially support their associate researchers for open access publishing (Segado‐Boj et al, 2022). If the authors who received financial support believe that it is reasonable for more frequently cited journals to demand higher APCs, they would select a parent journal and pay a higher APC.…”
Section: Discussionmentioning
confidence: 99%
“…This seems like a triple burden for scholars in the periphery who already lack resources and have a constrained research budget. In addition to not being able to access knowledge through traditional or legal pathways, they also seem to be unaware of the (illegal) solutions to their problems, which add up to the difficulties in paying the article processing charge associated with many OA, well-indexed, journals (Segado-Boj et al, 2022). In this sense, the democratizing role that Sci-Hub and other pirated document repositories claim to play has a limited effect and does not fully reach the Global South.…”
Section: Discussionmentioning
confidence: 99%